Evidence of SARS-CoV-2 Antibodies and RNA on Autopsy Cases in the Pre-Pandemic Period in Milan (Italy) - Lai, Alessia; Tambuzzi, Stefano; Bergna, Annalisa; Battistini, Alessio; Della Ventura, Carla; Galli, Massimo; Zoja, Riccardo; Zehender, Gianguglielmo; Cattaneo, Cristina (Frontiers in microbiology, 2022)
In this study, we analyzed blood samples obtained from 169 cadavers subjected to an autopsy from 1 October 2019 to 27 March 2020. The presence of anti-severe acute respiratory syndrome coronavirus 2 (anti-SARS-CoV-2) antibodies was searched by lateral flow immunochromatographic assay (LFIA) and ELISA tests and the SARS-CoV-2 RNA was tested in blood and available lung tissues by real-time PCR (RT-PCR) and droplet digital PCR (ddPCR). Five cases resulted in positives at the serological screening for anti-SARS-CoV-2. Three results were weakly positive for IgM while only one showed strong reactivity for IgG antibodies. The fifth subject (who died in December 2019) resulted positive for the ELISA test. The detection of SARS-CoV-2 RNA resulted in positive only in the blood and lung tissues of such cases. These data suggest that cadaveric blood may be a suitable substrate for the assessment of SARS-CoV-2 infection; moreover, they extend the observations of sporadic cases of SARS-CoV-2 infection in North Italy prior to the first confirmed cases.